Promoting secondary school students’ academic achievement in economics using think-pair-share and reciprocal instructional strategies in Lagos, State, Nigeria (2015)
This study determined the effects of Think Pair Share and Reciprocal Instructional strategies and moderating effect of students' learning styles on academic achievement of students in Economics. The results showed that there was a significant main effect of treatment on achievement (F(2.163) = 10.428; P < 0.05, partial η2 = 0.113); learning style had no significant main effect (F(1.163) = .759, P >.05, partial η2 = .05); instructional strategy> and learning styles had no significant interaction effect (F(2.163) = .616. P >.05, partial η2 = .008) on students' academic achievement in Economics. The major finding of this study was that both think-pair-share and reciprocal instructional strategies were more effective than the conventional instructional strategy in facilitating students' achievement in Economics. The study implies that effective teaching of Economics depends largely on mode of instruction. It is, therefore, recommended that, both think-pair-share and reciprocal instructional strategies should be employed in the teaching of Economics in Secondary school: pre-service and in- service teachers should be trained on effective use of the Two strategies, among others.